The impact of respondent attentiveness on reliability and validity. Issue 2 (4th March 2019) - Silber, Henning; Danner, Daniel; Rammstedt, Beatrice
ABSTRACT: This study aims to assess whether respondent inattentiveness causes systematic and unsystematic measurement error that influences survey data quality. To determine the impact of (in)attentiveness on the reliability and validity of target measures, we compared respondents from a German online survey ( N = 5205) who had passed two attention checks with those who had failed. Our results show that inattentiveness induces both random and systematic measurement error, which impacts estimates of the reliability and validity of multi-item scales. In addition, we conducted a sensitivity analysis, which revealed that the impact of inattentiveness on analyses can be substantial.